2011
DOI: 10.1016/j.physletb.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

QED effective action in Krein space quantization

Abstract: The one-loop effective action of QED is calculated by the Schwinger method in Krein space quantization. We show that the effective action is naturally fnite and regularized. It also coincides with the renormalized solution which was derived by Schwinger.Comment: 15 pages, Accepted for publication in Phys.Lett.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…9 It is shown that in Krein space method, the UV divergences of the Green function are removed. 2,[10][11][12][13][14][15] Interestingly, by considering the quantum metric fluctuation, the light-cone singularity can be also handled. 2,12,13,15,16 The propagator of Krein regularization is…”
Section: Introductionmentioning
confidence: 99%
“…9 It is shown that in Krein space method, the UV divergences of the Green function are removed. 2,[10][11][12][13][14][15] Interestingly, by considering the quantum metric fluctuation, the light-cone singularity can be also handled. 2,12,13,15,16 The propagator of Krein regularization is…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of the negative norm states was first studied by Dirac in 1942 [12]; Gupta and Bleuler in 1950 used such states to remove the infrared divergence in QED [13]. Carrying out the quantization in Krein space has followed in some papers: the vacuum energy vanishes and an infinite term does not appear in the calculation of the expectation value of T μν [14]; in the interaction QFT this method automatically removes the singular behaviors (ultraviolet) of Green's functions [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that quantization in Krein space removes all ultraviolet divergences of QFT except the light cone singularity [1,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%